Strategi Bertahan Pedagang Konvensional di Tengah Perkembangan Pasar Online (Studi Kasus pada Pedagang Konvensional di Pasar Nagari Air Bangis Kecamatan Sungai Beremas Kabupaten Pasaman Barat) - Lifia - Fitriana; Rinel Fitlayeni; Waza Karia Akbar (STKIP PGRI Sumatera Barat, 2021)
This research is motivated by the existence of an online market. Which makes the conventional market to be left behind and the income of traders to decline. The same is true for conventional traders in the Nagari Air Bangis market, Sungai Beremas District, West Pasaman Regency. The formulation of the research problem is how to survive conventional traders in the midst of the development of the online market. The theory used in this study is the theory of rational choice proposed by Coleman. This research approach is a qualitative approach with a descriptive type of research. The types of research data are primary and secondary data. There were 14 informants. Data collection methods are observation, in-depth interviews and document studies. To achieve the validity of the data using triangulation techniques. Meanwhile, the unit of data analysis is the individual with data analysis by Miles and Huberman, namely data reduction, data presentation, data presentation and conclusion drawing. From the results of the study, it can be concluded that there are conventional traders' survival strategies in the Nagari Air Bangis market, namely following the trend of goods being sold, displaying new goods on the front, giving discounts (discounts), and increasing social networks with buyers..